Srī Gurū Grantha Sāhiba jī dī kuñjī, arathāta, Wārāṃ Bhāī Guradāsa jī : saṭīka - Bishana Siṅgha (SAMP early 20th-century Indian books project ;)
Text, with interpretation of Wārāṃ, religious poetry by Bhai Guradāsa, ca. 1555-1629, poet and religious leader.